Strengthening nanostructured metals through dynamic recovery - Amanda P. Carvalho; Aoyan Liang; Megumi Kawasaki; Livia Cupertino-Malheiros; Paulo S. Branicio; Roberto B. Figueiredo (Journal of Materials Research and Technology)
Recovery plays distinct roles in nanostructured and coarse-grained metallic materials. While static and dynamic recovery usually soften work-hardened, coarse-grained materials, static recovery has been shown to strengthen nanostructured metals. This study extends this understanding by demonstrating that dynamic recovery can also strengthen nanostructured metals under deformation. Tensile, creep, and plane strain compression tests on nanostructured aluminum reveal a trend of increasing strain-hardening with decreasing strain rate and increasing temperature. Molecular dynamics simulations further indicate that sudden strain rate reductions lead to an initial drop in flow stress, followed by strain hardening. These findings suggest that dynamic recovery could serve as an effective strengthening mechanism for nanostructured metals, offering improvements in uniform elongation.